1997
DOI: 10.1055/s-0038-1656116
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of P-selectin as a Circulating Plasma Protein

Abstract: SummaryP-selectin is a 140 kD protein found in the α-granules of platelets and the Weibel-Palade bodies of endothelial cells. On cell activation it is expressed on the cell surface and also secreted into plasma. Whether the circulating soluble P-selectin (sP-selectin) originates from platelets, endothelial cells, or both, is not known. We studied the level of sP-selectin in diseases with different platelet counts, with or without evidence of endothelial cell activation. Endothelial cell activation was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
1
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(148 citation statements)
references
References 28 publications
11
131
1
5
Order By: Relevance
“…This higher concentration of sP-selectin observed in normal pregnancy is suggestive of increased platelet activation. Although both endothelial cells and platelets express P-selectin, previous studies have reported that sP-selectin is not primarily a product of the endothelium, but rather, that platelets are the major source of sP-selectin in normal controls 13,14 and in thrombotic and prethrombotic conditions 15 . Fijnheer et al 14 previously reported sP-selectin concentration per platelet to be a measure of endothelial cell activation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This higher concentration of sP-selectin observed in normal pregnancy is suggestive of increased platelet activation. Although both endothelial cells and platelets express P-selectin, previous studies have reported that sP-selectin is not primarily a product of the endothelium, but rather, that platelets are the major source of sP-selectin in normal controls 13,14 and in thrombotic and prethrombotic conditions 15 . Fijnheer et al 14 previously reported sP-selectin concentration per platelet to be a measure of endothelial cell activation.…”
Section: Discussionmentioning
confidence: 98%
“…Platelet mass was calculated by multiplying platelet count (Â10 9 /L) by mean platelet volume (fL). Concentration of sP-selectin per platelet was calculated by dividing the sP-selectin concentration (ng/mL) by the individual platelet count (Â10 9 /L), as described by Fijnheer et al 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Even if P-selectin has been recognized in endothelial cells it is apparent that the greater quantity if not all soluble P-selectin evolves from platelets [6]. It has been suggested that soluble P-selectin reflects platelet activity over a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, P-selectin is a marker of platelet activation which in turn is prerequisite for thrombosis (Serebruany et al, 1999a). Fijnheer et al (1997) have concluded that endothelial cell activation is associated with an increased P-selectin concentration per platelet. Elevated levels have been reported not only in AMI and unstable angina but also in stable angina.…”
Section: P-selectinmentioning
confidence: 99%